1982
DOI: 10.1111/j.1365-2222.1982.tb03132.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of allergy—has it changed?

Abstract: Summary A survey of the incidence of allergy in the entire population of a new‐town general practice is reported, comparing the year 1974 with 1979. A rise in the incidence of allergic complaints is noted in both sexes. However, hay fever and asthma continue to show a male dominance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 0 publications
3
15
1
Order By: Relevance
“…Previous reports [1,2] and our clinical experience show that the incidence of allergic disorders has been increasing. Considerable efforts have been made to find a reliable pre diction method for allergy during childhood.…”
Section: Introductionmentioning
confidence: 96%
“…Previous reports [1,2] and our clinical experience show that the incidence of allergic disorders has been increasing. Considerable efforts have been made to find a reliable pre diction method for allergy during childhood.…”
Section: Introductionmentioning
confidence: 96%
“…With age, rhinitis symptoms tend to become milder (252,275,721) and simultaneously the allergic skin reactivity decreases in the elderly (1039). Some studies found an increased prevalence of allergic rhinitis in young adults (1040)(1041)(1042)(1043)(1044)(1045)(1046).…”
Section: Natural Historymentioning
confidence: 99%
“…Several studies indicate that the prevalence of allergy is increasing, particularly in countries with a ''western lifestyle'' (1)(2)(3)(4)(5)(6). All of these studies were related to eczema or respiratory allergy, however.…”
mentioning
confidence: 99%